Bifonazole in vitro activity and its azole-parallel resistance in clinical yeast isolates - Czaika, V. A.; Tietz, H.J.; Schmalreck, A.F. (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
The susceptibility/resistance profile of bifonazole (BFZ) in 170 dermatophyte strains including azole parallel-resistance in 324 clinical yeast isolates was determined, additionally with impact on patient-relevant factors. Overall susceptibility to four azoles tested in parallel was 70%, with differences to both, the azoles, and species-specific for isolates from patients with superficial or invasive/systemic infections. 86% of the C. glabrata (n=166) isolates were susceptible to bifonazole, 76% were BFZ-susceptible to fluconazole-resistant C. glabrata (n=184) isolates, whereas 45% of the bifonazole-resistant strains (n=82) were susceptible to FLC. However, compared to voriconazole most of the other non-C. albicans Candida, and non-Candida species were less susceptible (< 50%) to bifonazole. As the other azoles tested, BFZ showed bimodular MIC-distribution. Susceptibility pattern analysis (SPA) demonstrated that isolates from antifungal agent pretreated patients had zero to significant less complete susceptible isolates (SP: SSSS) compared to non-treated patients. Furthermore, SPA revealed zero to fourfold parallel-resistance, species-specifically distributed, most prominently in C. glabrata and C. parapsilosis. Evaluation of azole susceptibility and two-way hierarchical clustering revealed a high grade of diversity and heterogeneity among the clinical C. glabrata isolates. A modified MIC assessment system was introduced to achieve a more realistic, well-arranged, and therapy oriented reporting of MIC in vitro data.